The Production Process of Pendap as an Integrated Science Learning Media: Ethnoscience Study of the Lembak Tribe Bengkulu Province - Ahmad Walid; Endang Widi Winarni; Fitri April Yanti (Scientiae Educatia: Jurnal Pendidikan Sains, 2022)
This study aims to reconstruct the original knowledge of the community in the pendap production process into scientific knowledge used as a medium for science learning. Data collection was carried out on Jalan Irian, Tanjung Agung Village, Sungai Serut District, Bengkulu City. The research method is descriptive qualitative with data collection techniques through observation, questionnaires, and interviews. The data obtained is then analyzed, verified, and reduced then constructed into scientific knowledge and interpreted into science concepts in science learning. The results of the study indicate that the process of making pendap by the community can be interpreted into scientific knowledge and implemented in science learning. This study concludes that the pendap production process is the community's original knowledge, which is used as a science learning medium.